Diagnostic ultrasound in surgery clinics - V. V. ZARETSKY (Archives of Acoustics)
The author presents a short survey of ultrasonic applications in diagnosis of various heart diseases, peripheral blood vessel disorders and abdominal pathologies before the operation and intraoperatively and in the treatment of various kinds of disorders. In the author's opinion ultrasound renders nowadays a great help to the surgeon and will become even more useful in the coming years.